Computational analysis of failure mechanisms in composite sandwich space structures subject to cyclic thermal loading - Venkatesan, K.R.; Stoumbos, T.; Inoyama, D.; Chattopadhyay, A. (Composite structures, 2021)
Accurate prediction of the thermal stability and durability of composite sandwich materials used in space structures remains a challenge due to the variability of thermal related material coefficients at different temperatures and the extensive use of adhesively bonded joint fittings. This paper presents an investigation into the thermomechanical performance of complex honeycomb core composite sandwich structures with bonded fittings exposed to extreme temperature ranges. First, detailed analyses are conducted to investigate the failure and predict the intrinsic nonlinear material properties of a specific aerospace-grade aluminum honeycomb core and carbon-epoxy composite face sheet. Sandwich panels with two types of bonded fittings are chosen to investigate nonlinear effects such as shear buckling and plastic deformation in the honeycomb core, and the progressive damage response in composite skins under different loading conditions. The nonlinear properties and modeling strategies are then incorporated in the subsequent analysis of a spacecraft’s thrust tube sandwich structure subject to cyclic thermal loading. The predicted damage and failure in the thrust tube section with an adhesively bonded cup fitting correlated with experimental observations. The current methodology offers a consistent technique for investigating the thermomechanical performance of sandwich structures with other configurations of bonded joints and fittings.